Influence traditional, traditionally-sectional and sectional forms of organization of lessons on physical education on a level of somatic health of students (1-4 courses). - Poproshaev O.V; Chumacov O.V; Kashynsky G.A (Kharkov National Pedagogical University, 2011)
The analysis of the author programs is conducted on physical education of students. 25 students were tested during 4th years. The indexes of somatic health of students are considered: anthropometric, functional indexes of the cardiovascular system, functional test with the dosed physical loading. Influence of forms of organization of educational process is set on an individual (somatic) level of health of students. It is set that the motive mode of student must make no less than 6 hours in a week (4 hours are practical employments, 2 hours is the health swimming).